2018
DOI: 10.1002/hep.30099
|View full text |Cite|
|
Sign up to set email alerts
|

Rituximab Is Ineffective for Treatment of Fatigue in Primary Biliary Cholangitis: A Phase 2 Randomized Controlled Trial

Abstract: Rituximab was safe over the 12-month study period but showed no evidence of effectiveness for the treatment of fatigue in PBC. Anaerobic threshold improvement was seen, potentially linking AMA with muscle bioenergetics dysfunction; however, this was not related to improvement in fatigue. Rituximab had some evidence of a beneficial effect on alkaline phosphatase levels in this largely ursodeoxycholic acid (UDCA)-responding, early-disease stage cohort. (Hepatology 2018; 00:000-000).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Regardless of why it arises, it is likely to hamper recovery from fatigue unless it is addressed. [49][50][51] Central Pathways: To generate symptoms in CLD, including fatigue, activation of peripheral signalling pathways must lead to changes within the brain. Numerous neurotransmitter systems and brain regions have been implicated in the regulation of central fatigue ( Figure 3); however, there is a growing body of evidence that links central fatigue to dysfunction in the basal ganglia within the brain.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Regardless of why it arises, it is likely to hamper recovery from fatigue unless it is addressed. [49][50][51] Central Pathways: To generate symptoms in CLD, including fatigue, activation of peripheral signalling pathways must lead to changes within the brain. Numerous neurotransmitter systems and brain regions have been implicated in the regulation of central fatigue ( Figure 3); however, there is a growing body of evidence that links central fatigue to dysfunction in the basal ganglia within the brain.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Modulators of T-cell function and of T-cell recruitment have been studied with negative results. Limited data have shown improvement in ALP with significant improvement in pruritus with rituximab but with no improvement in fatigue [79,80]. The risks of stem cell transplantation, which has been evaluated in several studies, has failed to show clinically significant benefit and does not appear to be worth the risks of such an invasive procedure.…”
Section: Immune System Modulationmentioning
confidence: 99%
“…Interleukin modulation with ustekinumab has also been found ineffective. B-cell depletion with rituximab lacks long-term efficacy and is not beneficial for the treatment of fatigue, but may improve pruritus [79,80]. Other biologic therapies including invasive measures such as stem cell transplantation have also lacked significant enough benefit to be worth the potential side effects.…”
Section: Other Agentsmentioning
confidence: 99%
“…67 However, a subsequent open-label study, including 14 patients, demonstrated only a mild improvement in liver tests (although pruritus decreased in 60%), 68 and a phase II randomised controlled trial with improvement in fatigue as the primary outcome failed to demonstrate efficacy at 12 months. 69 The overall conclusion is that rituximab has limited efficacy in PBC and is not recommended despite a good short-term safety profile.…”
Section: Immunological Agentsmentioning
confidence: 99%